Discovery and development of therapeutics from natural products against neglected tropical diseases - Brahmachari, Goutam (Natural product drug discovery., 2019)
Discovery and Development of Therapeutics from Natural Products against Neglected Tropical Diseases draws together research on medicinal agents from natural sources as starting points for the design of drugs against Neglected Tropical Diseases (NTDs). From the prediction of promising leads and identification of active agents, to the extraction of complex molecules, the book explores novel, economical and efficacious therapeutics for these diseases. It describes current research and the role of natural products, antimalarial compounds from marine natural products and sesquiterpene lactones, natural antileprotic agents, natural products with potential against Leishmaniasis, Trypanosomiasis and Dengue, and more. In addition, Quinoline and Isoquinoline alkaloids for developing new antiprotozoal agents are discussed, alongside anti-trypanosomatid heterocyclic compounds as structures for development. Combining the expertise of specialists from around the world, this volume aims to support and encourage researchers in the investigation of natural sources as starting points for the development of novel, safe and effective agents for use against neglected tropical diseases.